2020
DOI: 10.3390/met10060799
|View full text |Cite
|
Sign up to set email alerts
|

Wear of ZhS6U Nickel Superalloy Tool in Friction Stir Processing on Commercially Pure Titanium

Abstract: The use of electric arc or gas welding in the manufacture of titanium components often results in low quality welded joints due to large residual stresses and strains. A successful solution to this problem can be found in the application of friction stir welding. However, friction stir welding (FSW) of titanium alloys is complicated by rapid tool wear under high loads and temperatures achieved in the process. This paper studies the durability of a tool made of ZhS6U Ni-based superalloy used for friction stir p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 44 publications
0
18
1
1
Order By: Relevance
“…Все это требует поиска новых инструментальных материалов для сварки титановых сплавов. В этом качестве перспективным представляется жаропрочный сплав на основе никеля ЖС6У, который зарекомендовал себя при сварке высокопластичных (ВТ1-0, ОТ4-1) и среднепрочных (ВТ6) титановых сплавов [22,23].…”
Section: обработка металловunclassified
“…Все это требует поиска новых инструментальных материалов для сварки титановых сплавов. В этом качестве перспективным представляется жаропрочный сплав на основе никеля ЖС6У, который зарекомендовал себя при сварке высокопластичных (ВТ1-0, ОТ4-1) и среднепрочных (ВТ6) титановых сплавов [22,23].…”
Section: обработка металловunclassified
“…The first type is a product of mutual diffusion of the tool with the workpiece material, as evidenced by the nickel distribution map over the image area (Figure 7c). This type of inclusion is formed because, during the welding process, the tool quickly wears out and mixes into the stir zone [32]. The second type of inclusion is shown in Figure 8.…”
Section: Microstructure and Chemical Analysismentioning
confidence: 99%
“…A study of the process of treating commercially pure titanium by friction with stirring using a tool made of a nickel-based superalloy ZhS6U was presented in [9]. It was found that the transfer layer in titanium contained chemical elements of the ZhS6U alloy.…”
Section: Contributionsmentioning
confidence: 99%